An Investigation of the Utilisation and Barriers to the Social Acceptance of Alternative Building Technology in Housing Construction in South Africa - Adetooto, Johnson Damilola (Department of Construction Economics and Management, 2023)
Social acceptance and the adoption of Alternative Building Technology (ABT), with a focus on Sandbag Building Technology (SBT) in housing delivery, are imperative to bridging the ever increasing deficit in housing provision in South Africa, which stands at about 2.2 million units. However, ABT's adoption is influenced by issues, and its promotion is a difficult task in South Africa. This dissertation investigates the extent of use and the barrier to the social acceptance of ABT, focusing on SBT in housing construction in South Africa. It develops a framework to promote the social acceptability of ABT in housing delivery in South Africa. Specifically, this study has five objectives: (1) to determine the actor's perceptions of SBT as a sustainable and affordable housing solution in South Africa; (2) to identify and establish the critical drivers of social acceptance of SBT in South Africa; (3) to identify and establish the concomitant impediment to the social acceptance of SBT in South Africa; (4) to identify and establish the major strategies for the social acceptance of SBT in South Africa, and (5) to develop a framework for the uptake and social acceptance of SBT in South Africa. The objectives were achieved through a mixed research method that began with two focus group sessions with thirteen (13) randomly selected South African housing market players and end-users. Also, a questionnaire survey was conducted across South Africa's nine provinces and yielded 228 valid responses. The data were analysed using various methods such as inductive content analysis with NVivo, the Shapiro-Wilk test and Cronbach's Alpha, a mean score rating, the Kruskal-Wallis H Test, the Kaiser-Meyer-Olkin (KMO) sample adequacy measure and Bartlett's sphericity, and factor analysis. The hypotheses developed for the study were tested using the Partial least squares structural equation modelling (PLS-SEM) analysis technique. The findings revealed that the government-investor-related barrier, comprised of the government's lack of promotion of sandbags, their lack of interest and lack of finance schemes (bank loans, grants), is significant in impeding the social acceptance and use of SBT in South Africa. The study revealed that to promote the social acceptance of SBT there is a need for stakeholder integration; and that the government and the other South African housing market players need to support the adoption of SBT through the formation of strategic policy. More so, there is a need for effective education, training, availability of sandbag demonstration projects in all provinces, and knowledge sharing among South African housing stakeholders and end-users. The major benefits of SBT, which include its economic, construction and health- related benefits, should be communicated to South African housing stakeholders and the general public to promote its acceptance. This study provides a comprehensive framework for the social acceptance and adoption of sandbag technology in housing projects by drawing on the diverse opinions and practical experience of ABT experts and housing industry stakeholders in South Africa. In addition, this is the first and only effort to establish a framework for effectively adopting sandbag technology in South Africa, to provide inexpensive and sustainable housing. If completely implemented and approved, the framework will contribute to resolving South Africa's housing shortfall problem. Furthermore, the findings can be used as a policy tool and useful guidelines for government agencies, international organisations, and advocates interested in promoting a variety of ABTs such as sandbags in South Africa, to achieve more sustainable and affordable housing delivery.